Cerrados, natureza e sociedade: uma proposta de ensino-aprendizagem para alunos do ensino médio de Orizona, GO - Ribeiro, Ana Isabel (2019)
Thinking about Education from the relations between the world around us and the pedagogical practice is a challenge for teachers and researchers of Education. Understanding that the Cerrado is an important subject for the teaching of biology and other subjects, this study aims to analyze how a didactic sequence with historical, social, cultural and environmental elements can contribute to the critical learning of high school students. We used a qualitative methodological approach, in which the method was participant observation. Data collection was done through annotations, document analysis, questionnaires and focal groups, and the analysis of results was done using the Content Analysis technique. The main theoretical support that guides the research is Paulo Freire's critical pedagogy. The educational product resulting from this research is a didactic sequence based on the methodology of Delizoicov and Angotti (1990), known as Three Pedagogical Moments (Initial Problematization, Knowledge Organization and Knowledge Application), focused on High School, with the theme Cerrado’s Biodiversity and Culture. Applied to students of the 2.nd year of high school of a statal school in Orizona, Goiás, it consists of pedagogical interventions in the form of lectures, visits to the Memorial of Cerrado museum, interviews made by students with residents of Orizona County, plantation of seedlings and a presentation on the conservation of the Cerrado. The results of the pedagogical intervention were analyzed using the Content Analysis technique, from which it was possible to identify four categories of analysis: 1-Cerrado Biome, Culture and Society; 2-Cerrado Characteristics and Anthropization; 3-The classroom environment; 4-Conservation of the Cerrado. The indicators that led to these categories made it possible to identify the perceptions of the students about the object of study, as well as those related to classroom methodologies and awareness of Cerrado conservation.